2023
DOI: 10.1007/s00530-023-01083-0
|View full text |Cite
|
Sign up to set email alerts
|

An overview of deep learning techniques for COVID-19 detection: methods, challenges, and future works

Abstract: The World Health Organization (WHO) declared a pandemic in response to the coronavirus COVID-19 in 2020, which resulted in numerous deaths worldwide. Although the disease appears to have lost its impact, millions of people have been affected by this virus, and new infections still occur. Identifying COVID-19 requires a reverse transcription-polymerase chain reaction test (RT-PCR) or analysis of medical data. Due to the high cost and time required to scan and analyze medical data, researchers are focusing on us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 144 publications
0
3
0
Order By: Relevance
“…In-depth tests with CXR were carried out, and the results showed that the proposed model not only achieves an accuracy of 92.45% but also manages to successfully maintain the confidentiality of the data for a wide range of clients. Topff et al [ 72 ] developed a novel CNN [ 73 ] model for the classification of COVID-19, and they achieved remarkable outcomes in terms of a sensitivity of 0.87 and a specificity of 0.94. Lande et al [ 74 ] designed a DL model for the Omicron [ 75 ] variant of COVID-19 topic modeling.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In-depth tests with CXR were carried out, and the results showed that the proposed model not only achieves an accuracy of 92.45% but also manages to successfully maintain the confidentiality of the data for a wide range of clients. Topff et al [ 72 ] developed a novel CNN [ 73 ] model for the classification of COVID-19, and they achieved remarkable outcomes in terms of a sensitivity of 0.87 and a specificity of 0.94. Lande et al [ 74 ] designed a DL model for the Omicron [ 75 ] variant of COVID-19 topic modeling.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A detailed overview was done by the authors in [ 22 ] that discusses the different data types in COVID-19 detection using deep learning and machine learning. They have included the used data processing and the methodology for each study.…”
Section: Related Workmentioning
confidence: 99%
“…Despite the promising performance of deep learning models, challenges such as insufficient data, class imbalance, and the need for large datasets for training remain. These issues can impact the generalizability and reliability of the models [3] [4] 2 Context and related works Contact tracing has become a critical component in the fight against the COVID-19 pandemic, and advancements in equipment abilities have played a significant role in improving contact tracing efforts. The types of exposures that qualify someone as a contact can vary but generally include direct physical contact, sharing of a close physical space for a prolonged period, or direct interaction with the biological secretions of the infected individual according to the World Health Organization (WHO).…”
Section: Introductionmentioning
confidence: 99%